Analyzing The Implementation of Green-Economy Inclusive Strategy in East Java Province Through Urban Good Governance in Green-Economy Framework: The Case of Surabaya - Rizqi Shafira Chairunnisa; Hemalia Kusumadewi (East Java Economic Journal, 2024)
The global uncertainty has forced countries including Indonesia to look on ways to stabilize themselves, one of them being the implementation of green-economy development. The lack of inclusive and environmental-oriented policy has created an urgency for East Java Province to prioritize the green-economy implementation. Therefore this paper analyzes a possible implementation of green-economy through Surabaya City’s green-economy concept. This city is chosen due to its status being the only city in East Java to have the Green Sister City Surabaya-Kitakyushu program. This paper uses green economy city development which has four main dimensions which are; decision making process, Implementation Capacity, green economy system and the socio-ecological dimension. A qualitative-descriptive method will be used in this paper, along with a thematic analysis technique to deeply explain the topic at hand. The result of this research is a strategy that can be referenced by Surabaya to develop the green-economy city as the city already has its basis, especially in its society’s system in approaching green-economy aspects. Aside of that, this research also presents 3 strategies of implementing green-economy policies for cities throughout East Java Province. These strategies are intended for those cities to be able to take the first step in developing a green-economy city by deeper understanding of local context, policy & capacity development, and monitoring & evaluation.